The Praxis of Digital Information Consumption to Change Student Behavior During Pandemic - Danil Putra Arisandy; Muhammad Mukhlis (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2021)
This study aims to find out the consumptive practices of students as social media users and behavior changes felt due to frequent consumption of content from social media during the Covid-19 pandemic. In 2020, internet-based social media was also a new behavior and lifestyle in learning and teaching activities. The study used naturalistic inquiry methods, which resulted in writing or words and student behavior. Because to illustrate complex and concrete social realities, this study has interviewed IAIN Langsa students during the covid-19 pandemic. This research is descriptive of analytics by providing an overview of the objects studied. Sampling by snowball method makes it very easy for researchers to know students who are very active using social media. This study further used theory receptions where researchers analyzed students as social media users in the covid-19 pandemic in 2021, which is closely related to behavioral changes, namely from inclusive to exclusive or vice versa from exclusive to inclusive. This study shows that consumptive digital information practices through social media affect students, especially to changes in religious behavior, from inclusive behavior to exclusive behavior. However, this behavior is only limited to behavior in religious worship, not socio-cultural behavior. The findings of this study are that students who actively use social media can already distinguish between positive and negative content produced by online media consumed daily. After consuming social media content, students can choose and conduct studies before applying in everyday life.